Deploying decentralized, privacy-preserving proximity tracing - Troncoso, Carmela (2022)
[Excerpt] CONTACT TRACING IS a time-proven technique for breaking infection chains in epidemics. Public health officials interview those who come in contact with an infectious agent, such as a virus, to identify exposed, potentially infected people. These contacts are notified that they are at risk and should take efforts to avoid infecting others—for example, by going into quarantine, taking a test, wearing a mask continuously, or taking other precautionary measures. In March 2020, as the first wave of the COVID-19 pandemic was peaking, traditional manual contact tracing efforts in many countries were overwhelmed by the sheer volume of cases; by the rapid speed at which SARS-CoV-2 spread; and by the large fraction of asymptomatic, yet infectious, individuals. [...]